Pendampingan Pembentukan Siswa Berbudi Luhur Dalam Pengajian Kitab Taisirul Kholaq - Ulum, Miftachul; Mun’im, Abdul; Hadi, Abd; Zawawi , Abdullah (Jaanur ElBarik Indonesia, 2025)
This community service activity aims to provide guidance in developing students with noble character through the study of the Taisīrul Kholāq Book. The guidance activity was carried out using an educational and participatory approach, including reading the book, explaining the material, discussing it, and cultivating moral behavior in daily life. The results of the guidance showed an increase in students' understanding of noble moral values, such as politeness, discipline, respect for teachers and parents, and social responsibility. The study of the Taisīrul Kholāq Book has proven effective as a medium for character development because the material is simple, applicable, and relevant to students' lives.